Ultrathin metal-organic framework nanosheets (Cu-TCPP)-based isothermal nucleic acid amplification for food allergen detection - Jiale Gao; Xiaodong Sun; Yongxin Liu; Bing Niu; Qin Chen; Xueen Fang (Food Science and Human Wellness)
The rapid and accurate detection of peanuts and soybeans allergen is important to the food safety. In this study, Cu-TCPP nanosheet, a kind of ultra-thin metal-organic framework (MOF) was synthesized and applied in loop-mediated isothermal amplification (named Cu-TCPP@LAMP), which can inhibit the non-specific amplification by absorbing and precise temperature releasing of single primer. As thus, Cu-TCPP@LAMP can achieve high sensitivity and specific amplification of the target gene. As a result, peanut and soybean allergens genes contained in food were successfully detected with a favorable detection sensitivity (5 ng/μL for peanuts and 10 ng/μL for soybeans) and reliable repeatability (The coefficient of variation was 3.38% for peanuts and 3.33% for soybeans). Moreover, the established method was utilized for detection of several commercial products, and had a high consistency with the standard method. Apart from food allergens, this novel assay can be widely used in other areas, such as pathogen detection, tumor nucleic acid detection and so on.